Comparative corneal endothelial cell toxicity of differing intracameral moxifloxacin doses after phacoemulsification. Issue 3 (March 2020) - Chang, David F.; Prajna, N. Venkatesh; Szczotka-Flynn, Loretta B.; Benetz, Beth Ann; Lass, Jonathan H.; O'Brien, Robert C.; Menegay, Harry J.; Gardner, Susanne; Shekar, Madhu; Rajendrababu, Sharmila; Rhee, Douglas J.
Abstract : There was no increase in endothelial cell loss from a 500 μg compared with a 250 μg moxifloxacin dose given intracamerally in paired eyes undergoing phacoemulsification after exclusion of 2 outliers. Abstract : Purpose: To determine whether intracameral moxifloxacin 500 μg is noninferior to 250 μg for central endothelial cell loss (ECL) after phacoemulsification. Setting: Aravind Eye Care System. Design: Prospective masked randomized study. Methods: Eyes with bilateral nuclear cataracts, central endothelial cell density (ECD) of more than 2000 cells/mm 2, and ECD not differing between eyes by more than 200 cells/mm 2 underwent phacoemulsification at least 14 days apart. Intraoperatively, the first eye was randomized to receive either a 500 or 250 μg dose of moxifloxacin intracamerally and received the other dose for the second-eye surgery. Postoperative course was monitored at 1 day, 1 week, 1 month, and 3 months. Preoperative and 30-day and 90-day postoperative central ECD was determined by a reading center for a masked analysis of ECL at 3 months postoperatively. Results: Fifty eyes of 25 patients (aged 48 to 69 years) underwent uneventful surgery and had normal postoperative courses. The point estimate (PE) and 95% CI for the mean difference in % ECL between the 500 μg and 250 μg doses at 3 months postoperatively was 0.8% (−5.8%, 7.4%). Upon identifying and removing 2 outliers, noninferiority was proven with a mean difference of the PE, −2.2% (CI, −6.5%, 2.1%). Conclusions: Clinical and corneal endothelial cell were comparable in this study population for the 250 μg and 500 μg doses of intracameral moxifloxacin. Both doses were well tolerated clinically, supporting the use of the higher dose for improved antimicrobial coverage for the prevention of postoperative endophthalmitis.